Comparison of some Physiological Parameters Determined by Timing Consumption of Breakfast Meal among Adult Women - Ghadeer Hamid AL-Ardhi; Noran Jameel Ibraheem; Adil Mohammed AL-Maamory; Ali Mohammed Abd- Alameer (Institute of Medico-legal Publications Pvt Ltd, 2021)
Breakfast is the most important meal of the day. Eating a nutritious breakfast sets the tone for the day and promotes weight maintenance and weight loss by maintaining blood glucose levels and our metabolism. The purpose of the present study was to investigate the impact of timing breakfast consumption on some hematological parameters among some adult female student in college of science for women. Sample enrolled in the present study consist from 40 female with age arranged between 20-45 years , at an early -morning blood sample of 3 ml has been taken to measure the hemoglobin, RBC, BP, WBC, HCT% by hematological analyzer devise and body mass index was measured for subjects to estimate if there any difference between two study groups who take breakfast meal in early morning compared with those students who take breakfast meal at late morning. The results for total parameters measured were non-has significant difference between two study groups, so our conclusion the Keep eating breakfast meal at a limited time at (7 -9 am) and (9-11 am) in regularly have not changed clinically significant in some hematological and physiological testThe aim of study: This study was carried to indicate whether the timing consumptions of breakfast if influence on some classical hematological parameters in young women